A Comprehensive Research on Antibiotic Resistance Genes in Microbiota of Aquatic Animals - Hong, Bin; Ba, Yongbing; Niu, Li; Lou, Fei; Zhang, Zhaohuan; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
The occurrence of antibiotic resistance genes (ARGs) as emerging contaminants is of continued concern for human health. Antibiotics used in aquaculture have promoted the evolution and spread of ARGs. This study aimed to investigate the occurrence of 37 ARGs conferring resistance to six classes of antibiotics in 94 aquatic animals from five cities in southeast coast of China. The results showed that floR, sulII, sulI, strB, strA, aadA, and tetS were identified as the prominent ARGs with the high detection frequencies ranging from 30.9 to 51.1% in total samples. Then relative expression amount of seven prominent ARGs quantified by qPCR, ranging from 0.003 to 0.065. The tetS was the most abundant ARG among the seven ARGs. Though aadA was the second highest detection frequency of ARGs, it was the lowest expression amount ARG. The occurrences and abundances of ARGs in freshwater aquatic animals were greater than those in marine, reflecting the discrepancy of cultivation pattern between the freshwater and marine aquaculture. Shanghai was considered as the most prevalent site with 16 ARGs, and Ningbo merely contained 9 ARGs without of β-lactam ARGs and quinolone ARGs, showing variations of ARGs with geographical location. Eight kinds of sulfonamides and one chloramphenicol residues were further measured in samples from Shanghai. Interestingly, no target antibiotics were found, but sulfonamides resistance genes (sulI, sulII) and chloramphenicol resistance genes (floR) persisted at aquatic animals in the absence of selection pressure. Our research firstly shows comprehensive information on the ARGs in skin microbiota of aquatic animals, which could provide useful information and a new insight for better understanding on the ARGs dissemination in aquatic animals.